Analysis of air-, moisture- and solvent-sensitive chemical compounds by mass spectrometry using an inert atmospheric pressure solids analysis probe. Issue 1 (February 2018) - Mosely, Jackie A; Stokes, Peter; Parker, David; Dyer, Philip W; Messinis, Antonis M
A novel method has been developed that enables chemical compounds to be transferred from an inert atmosphere glove box and into the atmospheric pressure ion source of a mass spectrometer whilst retaining a controlled chemical environment. This innovative method is simple and cheap to implement on some commercially available mass spectrometers. We have termed this approach inert atmospheric pressure solids analysis probe ( i ASAP) and demonstrate the benefit of this methodology for two air-/moisture-sensitive chemical compounds whose characterisation by mass spectrometry is now possible and easily achieved. The simplicity of the design means that moving between i ASAP and standard ASAP is straightforward and quick, providing a highly flexible platform with rapid sample turnaround.